Characteristics of White Duck Mojosari and its Future Development for Commercial Duck Meat - Suparyanto, Agus (Indonesian Bulletin of Animal and Veterinary Sciences, 2003)
White duck Mojosari will own the good enough prospect when used as by component in forming of duck meat type. Egg production average was 224 eggs per bird per year, and its was competed with brown plumage. Average of egg weight is 65.15 ± 4.84 g, the length of egg is 54.95 ± 2.49 mm and wide surface of egg is 45.66 ± 2.33 mm. White plumage for laying duck type perhaps will be more a lot of constraint. Farmer habit for color pattern believed, that was as proudly varieties breeder on the each area. Serati duck still a lot of constraint because the consumer demand is more like with white performance and cleanness product. This condition was opinion by existence of chicken broiler which enough modern skill and progress in developed. The solution of overcome is crossing between white plumage duck and white plumage muscovy drake will very help to get the product desired by consumer. Expected of Serati duck could be developed for farm breeder industry and opportunities for the farmer business in villages.   Key words: Mojosari duck, feather color pattern, Serati, commercial